Effect of Furnace Loading Method on Deformation Consistency of Constant-depth Tooth Hypoid Gear in Heat Treatment - Yimin Mo; Junjian Yang; Yueqi Wang; Chong Xie; Jie Liu; Yaohang Liang (Jixie chuandong)
The constant-depth tooth hypoid gear is one of the important parts of the main reducer. The distortion of consistency directly affects the consistency of the gear contact area. In order to facilitate the control of the consistency of the heat treatment distortion of the constant-depth tooth，the gear heat treatment distortion under different furnace loading methods is studied. The study shows that the distortion of the main teeth at the edge position is slightly larger than the center； the deformation of the main bottom layer is significantly lower than that of the upper and middle layers； the deformation consistency of the sparse charging gear is significantly lower than that of the intensive loading furnace. At the same time, the tooth mounted charge frame is improved, the basis for the optimization of heat treatment fixture and improve the gear heat treatment distortion consistency is provided, some suggestions on improving the heat treatment distortion consistency of the gear are put forward.